Peningkatan Keaktifan Belajar Siswa Muatan Pelajaran IPA Melalui Model Pembelajaran Experiential Learninng - Fitriana Al Sabaah (Universitas Negeri Makassar, 2024)
The purpose of this study was to determine the application of the Experientnial Learning model in increasing the activeness of science learning of grade V students at SD Negeri 03 Bongas. The type of research used is class action research. The implementation of this research through a process consisting of four stages, namely planning, action, observation, and reflection. This research procedure was carried out in two cycles, namely the first cycle and the second cycle. Each cycle consists of 2 meetings. In this study, the subjects in this study were grade V students with a total of 28 students consisting of 12 male students and 16 female students. Data collection in this study was carried out by observation and documentation. The data analysis technique for the learning process observation sheet was carried out by calculating the percentage of the class average. Based on the results of the study, it can be concluded to answer the question that the Experiential Learning model can increase the activeness of science learning of fifth grade students of SD Negeri 03 Bongas. The results showed that student learning activeness in science subject content increased after the Experiential Learning model was applied in class V. This is indicated by an increase in the average percentage of students' learning activeness in class V. This is indicated by an increase in the average percentage of observations of student activeness in pre-action of 58.02%, in cycle I to 70% and increased again in cycle II to 83.57%.